THU0536 Knowledge of and expectations about functional restoration program for chronic low back pain are often false: a mirror survey of 40 patients and 59 physicians in 2017. (12th June 2018) - Pierre, L.; Bailly, F.; Assadourian, M.; Foltz, V.; Potel, A.; Morardet, L.; Ascione, S.; Le Ralle, M.; Dupeyron, A.; Ibrahim, N.; Griffoul-Espitalier, I.; Duplan, B.; et al.
Abstract : Background: Functional restoration programs (FRP) are multi-disciplinary programs that have demonstrated their effectiveness in chronic low back pain (CLBP) but they appear to be little known by patients and/or physicians. Objectives: To assess the knowledge and expectations of CLBP patients and physicians about FRP. Methods: Multicenter cross-sectional study in 2017 in 6 tertiary-care hospitals in France. Consecutive patients with CLBP (more than 6 weeks) who were seen for their CLBP were included. Physicians (rheumatologists or general practitioners, GPs) who had referred at least 5 patients to the tertiary-care centres were sent a survey. Patients and physicians were asked about their knowledge and expectations of a FRP. Results were scored as 'correct' regarding health professionals involved in the FRP, if both doctors and (physiotherapists or physical activity coach) were ticked; and 'correct' for duration if 3 to 6 weeks. Expectations regarding the FRP were rated on a list of potential expectations on a scale of 0–10. Expectations were scored ' correct' if return to work was scored ≥7/10, and 'fully correct' if physical activity and pain management, but not 'healing' were also expected. Responses were then compared between patients and physicians by Chi 2 test. Results: Of 172 patients, median age 48 years (IQR 38–58), median CLBP duration 5 years (IQR 2–10), 60.0% women: 110 (64.0%) had no knowledge of FRP; 22 had already participated in an FRP. The remaining 40 patients were compared to physicians (figure 1). Of 80 physicians, 42.5% GPs and 53.7% rheumatologists, 57.5% women: 21 (26.2%) had no knowledge of FRP (p value<0.0001 vs patients). The remaining 59 were compared to the 40 patients. Knowledge of FRP health professionals was 'correct' for 13/40 (32.5%) patients vs 41/59 (69.5%) physicians (p=0.0003); and knowledge of duration was 'correct' for 26/40 (65.0%) vs 46/59 (78.0%) physicians (p=0.15). Expectations were 'correct' for 21/40 (52.5%) patients vs 44/59 (74.6%) for physicians (p=0.02), and 'fully correct' for 9/40 (22.5%) patients vs 16/59 (27.1%) for physicians (p=0.6). Conclusions: FRP was largely unknown to patients with CLBP. Even those who were aware of the FRP did not know what to expect. While physicians' knowledge and perception of the FRP was better, there was still a lack of knowledge and therefore a likely underutilization or misuse of the FRP. Information campaigns are needed. Disclosure of Interest: None declared